Advantage of tacrolimus/mycophenolate mofetil regimen for cytotoxic T cell-mediated defence and its inhibition by additive steroid administration in high-risk liver transplant recipients. (11th January 2016) - Uemoto, S; Ozawa, K; Kaido, T; Mori, A; Fujimoto, Y
Summary: Our previous work revealed that the recipients with the highest pre-existing numbers of CD8 + effector T cells (TE ) [hyperparathyroidism (HPT)E recipients] occupied approximately 30% of adult transplant recipients performed in our hospital. HPTE recipients demonstrated very poor clinical outcome compared with the remaining 70% of recipients with the lowest pre-existing TE (LPTE recipient). This study aimed to clarify the best combined immunosuppressive regimen related to function of cytotoxic T lymphocytes (CTLs) for HPTE recipients. Eighty-one HPTE recipients were classified into three types, according to the immunosuppressive regimens: type 1, tacrolimus (Tac)/glucocorticoid (GC); type 2, Tac/mycophenolate mofetil (MMF)/GC; and type 3, Tac/MMF. Frequencies of severe infection, rejection and hospital death were the highest in types 1 and 2, whereas the lowest occurred in type 3. The survival rate in type 3 was the highest (100%) during follow-up until post-operative day 2000. Regarding the immunological mechanism, in type 1 TE perforin and interferon (IFN)-γ were generated through the self-renewal of CD8 + central memory T cells (TCM ), but decreased in the early post-transplant period due to marked down-regulation of interleukin (IL)-12 receptor beta-1 of TCM. In type 2, the self-renewal TCM did not develop, and the effector function could not be increased. In type 3, in contrast, the effectors and cytotoxicity were correlated inversely with IL-12Rβ1 + TCM levels, and increased at the highest level around the pre-transplant levels of IL-12Rβ1 + TCM . However, the immunological advantage of Tac/MMF therapy was inhibited strongly by additive steroid administration.